Research Methods and Methodology - Sakyi, Kwesi Atta; Musona , David; Mweshi , Geoffrey (Advances in Social Sciences Research Journal, 2020)
Research is an interesting field of study which every student or scholar has to encounter in the course of time. The objective of this paper is to explore the various approaches to research so that students can gain insight and understanding. This paper attempts a review of the various approaches to research so that the reader can make an informed choice. The paper is based on secondary sources plus the author’s own experience borne from decades of teaching. This paper does not claim to have exhausted the list of approaches to research as there are far many approaches than can be dealt with in a short review communication. However, it is hoped it will lay a foundation for further research into the field by readers